Factors Associated with Glycemic Control Among Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study - Wahyuni, Sri; Prasetyowati, Christina Dewi; Pujiastutik, Yanuar Eka (STIKep PPNI Jawa Barat, 2023)
Aims: Even though the prevalence of type 2 diabetes mellitus in Indonesia continues to increase, research data on glycemic management, which is the primary strategy for reducing complications of diabetes mellitus, is still limited. In this study, an evaluation of glycemic control status and related factors was conducted in adult patients with type 2 diabetes mellitus. Methods: This research was a cross-sectional study with 115 type 2 diabetes adults who came to the Hospital in Kediri for treatment. Data was collected using the UK Diabetes and Diet Questionnaire (UKDDQ) questionnaire, which consists of 24 questions and the Godin Leisure-Time Exercise Questionnaire (GLTEQ), along with a blood glucose check between July and August 2023. The glycemic level was assessed using a random blood glucose level, and 'poor glycemic control' was defined when the blood glucose level was >200 mg/dL. SPSS was used for descriptive analyses and inferential statistics by chi-square test to analyze the relationship between patients glycemic control status and its relevant risk factors, including demographics, dietary control, and physical activity. Results: Only 26.1% of type 2 diabetes mellitus patients at Aura Syifa Kediri Hospital have good glycemic control. In bivariate analysis, gender, education, control status of diet, and physical activity (P values 0.05) were significantly correlated with glycemic control. Meanwhile, age, marital status, employment status, and duration of diabetes mellitus (p-value> 0.05) were not associated with glycemic control. Conclusion: The prevalence of good glycemic control in type 2 diabetes patients remains low. Based on this research, we found that gender, education, diet control, and physical activity were influencing factors in this problem. Publicity and education regarding the importance of glycemic control should be developed for type 2 diabetes patients, and targeted interventions should be made for risk groups.